2004
DOI: 10.1007/bf02984562
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow abnormalities induced by transient hypothyroidism after thyroidectomy —analysis by Tc-99m-HMPAO and SPM96—

Abstract: 99mTc-HMPAO SPECT and SPM96 analysis demonstrated a significant rCBF decrease in the parietal lobe and part of the occipital lobe in patients with induced transient hypothyroidism after thyroidectomy. This phenomenon might contribute to understanding of the depressive state. Recovery of rCBF after thyroid hormone replacement was confirmed in some patients. However, rCBF improvement did not always occur in every patient during the follow up period. The reversibility of rCBF in transient hypothyroidism may be de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 23 publications
5
27
0
Order By: Relevance
“…Indeed, our subjects demonstrated depressive and anxiety symptoms, as well as psychomotor slowing, when markedly hypothyroid. These findings support other studies where depression, anxiety, and psychomotor slowing were found during similar hypothyroid states (Denicoff et al, 1990;Constant et al, 2001;Nagamachi et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Indeed, our subjects demonstrated depressive and anxiety symptoms, as well as psychomotor slowing, when markedly hypothyroid. These findings support other studies where depression, anxiety, and psychomotor slowing were found during similar hypothyroid states (Denicoff et al, 1990;Constant et al, 2001;Nagamachi et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…These studies included mild hypothyroidism in one study, which might in itself have a different effect on the brain than severe, transient hypothyroidism (Krausz et al, 2004), and marked, transient hypothyroidism (Nagamachi et al, 2004) similar to our subjects. Like us, each of these groups of investigators showed regional decreases in radiotracer activity; and our data do, in fact, corroborate one (but no other) finding by Nagamachi et al (2004) of decreased activity in parts of the occipital lobes. However, unlike our group, neither of these groups of investigators demonstrated areas of increased tracer accumulation.…”
Section: Discussionmentioning
confidence: 91%
“…Thyroid dysfunction-induced mood changes may be partly due to cerebral blood flow (CBF) abnormalities, as demonstrated in patients with transient hypothyroidism studied with 99 mTc-HMPAO SPECT versus normal controls (38). Regional CBF alterations have been detected in the bilateral parietal lobes and in the bilateral occipital lobes, which extended to the prefrontal cortices as hypothyroidism worsened.…”
Section: Effects On Lipidsmentioning
confidence: 98%
“…However, fluorodeoxyglucose (FDG) and oxygen-15-labeled water studies, in similar patients, showed lower global brain glucose metabolism and flow. Hypothyroidal patients were also significantly more depressed, anxious and psychomotor slowered than euthyroidal subjects (Nagamachi et al, 2004;Constant et al, 2001). …”
Section: Hypothyroidism Depression and Brain Imagingmentioning
confidence: 88%